A STUDY OF STUDENTS’ ENTREPRENEUR CONCEPTS AND INTERESTS IN SUSTAINABILE LEARNING CONCEPT IN SPERMATOPHYTA MATERIALS OF STUDY - Rizqiyah, Kana; Hartadiyati W.H, Eny (Unnes Science Education Journal, 2017)
Based on Curriculum 2013, science learning process should apply an integrated concept. This study aims to investigate the effects of learning sustainability charged on spermatophyta material by explored local plants in Muria’s mountains to understand the concept and interest of entrepreneur students in class X. Implementation of research conducted on even semester of academic year 2016/2017 with research population of class X MIPA in one SMA Negeri in Kudus District. The sample used is class X MIPA 5 as experiment class and class X MIPA 7 as control class. Purposive sampling and nonequivalent control group design used as sampling techniques. The results of data analysis show that there is an increase in concept understanding in experimental class and control class. The experimental class’ retention is higher than control class, the control class is in low category while in the class in medium category. Student entrepreneur's interest in experiment class was higher than control class and t-test showed significant difference (p <0.05).